Peru - Recent Economic Development in Infrastructure : Volume 2. Investing in Infrastructure as an Engine for Growth - Spending More, Faster, and Spending Better - World Bank (Washington, DC, 2013)
This report provided the Government of Peru with a comprehensive strategic assessment of three key infrastructure sectors: water/sanitation, transport and electricity, and to propose selected recommendations on how the Government could improve the performance of these sectors. Peru's public expenditure framework shows some rigidities, a number of which were introduced when fiscal resources were scarce or, more recently, because of concerns about a possible risk of inflation. The implementation of the stimulus package has required a laborious transition to remove bottlenecks to faster public spending, sometimes at the risk of affecting the mechanisms that help ensure the quality of public expenditures. The Peruvian authorities have been able to accelerate public investments in infrastructure but little thinking has been dedicated to improving the efficiency and effectiveness of such investments. The report concludes that Peru should focus on: prioritizing infrastructure investments through improved planning, promoting efficiency in infrastructure delivery, enhancing sub-national governments' capacity with respect to infrastructure, and leveraging the participation of the private sector.